Automated Publish-Subscribe Middleware Configuration with M2etis - Wahl, Andreas Maximilian; Fischer, Thomas; Lenz, Richard (Proceedings of the 8th ACM International Conference on Distributed Event-Based Systems, 2014)
We present Massive Multiuser Event Infrastructure (M2etis), a configurable publish-subscribe middleware. M2etis uses discrete-event simulations and regression methods to translate declarative descriptions of event types in terms of the application domain to an optimal configuration. Configuration decisions are based on the Quality-of-Service (QoS) requirements of the application and are conducted by a configuration component at design-time to minimize performance impacts at run-time. The demonstration shows how the M2etis configuration workflow can be applied to the application domain of Massively Multiplayer Online Games (MMOGs). We explain the configuration workflow as conducted by the M2etis configuration component and illustrate how it can be integrated into the development lifecycle of distributed applications. © 2014 Authors.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.automa_7
Keywords: event semantics; massively multiuser virtual environments; publish subscribe systems

Automated Quality-of-Service-aware Configuration of Publish-Subscribe Systems at Design-Time - Fischer, Thomas; Wahl, Andreas Maximilian; Lenz, Richard (Proceedings of the 8th ACM International Conference on Distributed Event-Based Systems, 2014)
Configurable publish-subscribe middleware provides efficient support for the diverse Quality-of-Service (QoS) requirements of large-scale distributed applications. However, choosing the optimal middleware configuration to suit a specific application primarily remains a manual task within the responsibility of application developers. Existing configurable middleware approaches either do not allow extensive configuration or lack the possibility to specify QoS requirements in a domain-specific terminology. In this paper we present a novel methodology for the QoS-aware configuration of publish-subscribe middleware, which relies on discrete-event simulations and supervised learning techniques to automatically translate declarative descriptions of the application domain to an optimal configuration. The configuration is conducted at design-time to minimize possible run-time impacts. We implemented a design-time configurable middleware and evaluated the quality of the automated configuration workflow as well as the performance of event dissemination. Our results show that simulation experiments in conjunction with regression methods can be used to reliably derive optimal middleware configurations without further user interaction. We clarify that extensive design-time configurability does not compromise run-time performance and suits the requirements of demanding applications. © 2014 ACM.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD6.automa
Keywords: design-time configuration; event semantics; publish-subscribe; quality-of-service

Event semantics in event dissemination architectures for massive multiuser virtual environments. - Fischer, Thomas; Lenz, Richard (Proceedings of the Fourth ACM international Conference on Distributed Event-Based Systems, 2010)
As distributed applications in many domains grow more and more to a global scale, Massive Multiuser Virtual Environments (MMVEs) emerged in the gaming industry over the last years with an enormous monetary impact. Current architectures use centralized approaches, which obviously do only scale to a certain point. As recent research in this field has shown, the potential to improve scalability beyond this point rests in distributed event based architectures as well as the exploitation of event semantics to optimize these architectures. In this paper, we propose an event classification aimed at exploiting event semantics for performance optimization of MMVE architectures. © 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.events

Exploitation of Event-Semantics for Distributed Publish/Subscribe Systems in Massively Multiuser Virtual Environments. - Fischer, Thomas; Daum, Michael; Irmert, Florian; Neumann, Christoph; Lenz, Richard (In Proceedings of the 2010 international Symposium on Database Engineering & Applications, 2010)
Triggered by the fast evolving technical capabilities for implementing distributed global scale applications, online games have grown to a huge industry in recent years. Particularly, Massive Multiuser Virtual Environments (MMVEs), which allow for simultaneous activity of thousands of players in a virtual world, have been tremendously successful. Current architectures, however, use centralized approaches, which obviously do not scale beyond a certain point. Distributed event-based systems are a promising approach to reach both, performing and scalable architectures. The potential of this approach can only be fully exploited if event semantics is used to optimize event handling. Existing approaches actually do this to some degree, but typically in a very application specific manner. There is no generally applicable framework for classifying events according to their relevant semantic properties. In this paper, we propose a generally applicable classification of events as a first step on the way to exibly adaptable generic event management systems. We exemplify the relevance of our semantic properties by classifying typical events in an existing MMVE. We discuss existing optimization strategies based on our semantic classification and outline a corresponding architecture. Copyright 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.exploi

Improving data quality of routine data for clinical research - Fischer, Thomas; Lenz, Richard; Münster, Tino; Lauterwald, Frank; et al. (Tagungsband, 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.IMMD.IMMD6.improv

Integration of dynamic AOP into the OSGi service platform - Irmert, Florian; Lauterwald, Frank; Bott, Matthias; Fischer, Thomas; Meyer-Wegener, Klaus (Proc. 2nd Workshop on Middleware-Application Interaction, 2008)
The ability to adapt to different computing environments or external changes is an important requirement for both stationary and mobile computing. Without this ability, all requirements have to be foreseen, which is often not possible in practice. Classical software engineering approaches often lead to redeployment or even software migration. Therefore loosely coupled software design and a dynamic adaptation model are required. Dynamic aspect-oriented programming (d-AOP) in conjunction with service oriented programming is well suited to face this demand. One well known approach providing a service-oriented component model is the OSGi Service Platform. This paper introduces our approach to combine an OSGi Framework with d-AOP to establish dynamic adaptation of core concerns as well as crosscutting concerns. Seamless integration of current d-AOP frameworks is managed by mapping aspect deployment and undeployment to OSGi bundle lifecycle operations without affecting the deployment model. Unlike former proposals, this approach retains the strict separation of bundles as mandated by OSGi. Copyright 2008 ACM.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.integr
Keywords: Aspect mechanism; Aspect weaving; Aspect-oriented programming; Crosscutting concerns; Dynamic adaptation; Modularization; OSGi framework; Reuse; Software components

M2etis: An adaptable Publish/Subscribe System for MMVEs based on Event Semantics - Fischer, Thomas; Held, Johannes; Lenz, Richard (Proceedings BTW 2011 - Workshops und Studierendenprogramm, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.m2etis

MATINEE: A Quality-of-Service-aware Event Semantics Modeling Language - Wahl, Andreas Maximilian; Fischer, Thomas; Lenz, Richard (2014)
UnivIS-Import:2016-06-30:Pub.2014.tech.IMMD.IMMD6.matine

OXDBS – Extension of a native XML Database System with Validation by Consistency Checking of OWL-DL Ontologies - Neumann, Christoph; Fischer, Thomas; Lenz, Richard (Proc of the 14th International Database Engineering & Applications Symposium, 2010)
Native XML database systems provide mature technology for persisting XML data and documents. Ontologies are often represented as XML-based documents like OWL-DL ontologies which allow for semantic consistency checking by formal description logic. Artificial intelligence provides reasoners as IT-support for consistency checking. Currently there exists no native XML database system which integrates logic reasoning for semantic consistency as addition to syntactic schema validation. The OXDBS project integrates a reasoner into a native XML database system, thus, allowing to assert consistency of ontological data at the most basic tier in an application environment. Copyright © 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.oxdbse
Keywords: ProMed

OXDBS - Extension of a native XML Database System with Validation by Consistency Checking of OWL-DL Ontologies - Neumann, Christoph; Fischer, Thomas; Lenz, Richard (2010)
Native XML database systems provide mature technology for persisting XML data and documents. Ontologies are often represented as XML-based documents like OWL-DL ontologies which allow for semantic consistency checking by formal description logic. Artificial intelligence provides reasoners as IT-support for consistency checking. Currently there exists no native XML database system which integrates logic reasoning for semantic consistency as addition to syntactic schema validation. The OXDBS project integrates a reasoner into a native XML database system, thus, allowing to assert consistency of ontological data at the most basic tier in an application environment.
Keywords: Semantic Web and Databases; Logic and Databases; Medical Systems; Data Quality and Semantics

Runtime adaption in a service-oriented component model - Irmert, Florian; Fischer, Thomas; Meyer-Wegener, Klaus (Proceedings of the 2008 international workshop on software engineering for adaptive and self-managing systems, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.runtim

The Adaptation Model of a Runtime Adaptable DBMS - Irmert, Florian; Fischer, Thomas; Lauterwald, Frank; Meyer-Wegener, Klaus (Dataspace: The Final Frontier, 2009)
Nowadays maintenance of database management systems (DBMSs) often requires offline operations for enhancement of functionality or security updates. This hampers the availability of the provided services and can cause undesirable implications. Therefore it is essential to minimize the downtime of DBMSs. We present the CoBRA DB (Component Based Runtime Adaptable DataBase) project that allows the adaptation and extension of a modular DBMS at runtime. In this paper we focus on the definition of an adaptation model describing the semantics of adaptation processes. © 2009 Springer Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.theada

The Storage System of a Runtime Adaptable DBMS - Irmert, Florian; Fischer, Thomas; Lauterwald, Frank; Meyer-Wegener, Klaus (Software Engineering for Tailor-made Data Management, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD6.thesto
Keywords: Software Engineering; Data Management; Software Product Lines; Embedded Systems

Towards an adaptive event dissemination middleware for MMVEs - Fischer, Thomas; Held, Johannes; Lauterwald, Frank; Lenz, Richard (Proceedings of the 5th ACM international conference on Distributed event-based system, 2011)
The Massive Multiuser Event InfraStructure (M2etis) project is aimed at a generic middleware that supports the optimization of event dissemination based on a multidimen- sional semantic classification of event types. In this paper, we introduce the M2etis system architecture with its core concepts. © 2011 Authors.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.toward
Keywords: m2etis; debs; middleware; event; semantics

Towards Exploitation of Event Semantics in Event Dissemination Architectures for Massive Multiuser Virtual Environments - Fischer, Thomas; Lenz, Richard (DEBS PhD Workshops, Fourth ACM international Conference on Distributed Event-Based Systems, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD6.toward_2